2007
DOI: 10.2807/esw.12.41.03284-en
|View full text |Cite
|
Sign up to set email alerts
|

European Surveillance of Antimicrobial Consumption (ESAC): outpatient antibiotic use in Europe, 1998-2005

Abstract: †These authors contributed equally to this work.Objectives: To describe total outpatient systemic antibiotic use in Europe from 1997 to 2009 and to analyse statistically trends of total use and composition of use over time.Methods: For the period 1997-2009, data on outpatient use of systemic antibiotics aggregated at the level of the active substance were collected and expressed in defined daily doses (WHO, version 2011) and packages per 1000 inhabitants per day (DID and PID, respectively). Outpatient antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 5 publications
(6 reference statements)
2
42
1
3
Order By: Relevance
“…In our study, the most frequently used antibiotic was the combination of amoxicillin plus clavulanic acid, as observed in primary care [1,14]. This finding confirms that hospital antimicrobial use tends to display a similar distribution pattern to that observed in the ambulatory use [4].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In our study, the most frequently used antibiotic was the combination of amoxicillin plus clavulanic acid, as observed in primary care [1,14]. This finding confirms that hospital antimicrobial use tends to display a similar distribution pattern to that observed in the ambulatory use [4].…”
Section: Discussionsupporting
confidence: 78%
“…In 2005, Italy ranked third among European countries with the highest consumption of antibiotics in outpatient care [14], and a recent literature review of studies published in USA, Canada, north-central Europe and Italy found that Italy also has one of the highest paediatric outpatient antibiotic prescription rates [15]. Although a strong positive correlation between the extent of antibiotic consumption in outpatient and inpatient care has been shown [4], no national data on hospital consumption have been collected in Italy up to now, and no national policies on the prudent use of antibiotic have been implemented.…”
Section: Discussionmentioning
confidence: 99%
“…22 It was desirable to include GPs with experience of several strategies, and these were more likely to be found in countries with national antibiotic campaigns.…”
Section: Methodsmentioning
confidence: 99%
“…3 The percentage of antibiotics prescribed unnecessarily is unknown, but it is believed that a number are used to treat minor respiratory tract infections (RTIs). 4 These conditions -such as the common cold, sore throat, acute otitis media and acute bronchitis -are often of viral aetiology and there is no compelling evidence to support the use of antibiotics in their treatment. [5][6][7][8] It has been shown that using antibiotics to treat these conditions does not prevent serious complications in otherwise healthy adults.…”
Section: Introductionmentioning
confidence: 99%